Retrospective study on chemotherapy–induced anaemia: incidence, treatment patterns and outcomes in a tertiary care hospital in South India - Sowmiya, D.; Suthish, B.; Bhuvaneswari, K. (International Journal of Basic & Clinical Pharmacology, 2026)
Background: Chemotherapy-induced anaemia (CIA) is a common complication in cancer patients and can negatively affect treatment continuity and quality of life. The severity of anaemia may vary depending on the chemotherapeutic drug class. This study aimed to evaluate the incidence, severity, management, and outcomes of CIA in a tertiary care hospital. Methods: A retrospective observational study was conducted among 100 cancer patients who received chemotherapy between January 2024 and December 2024. Demographic data, cancer diagnosis, chemotherapy regimens, haemoglobin levels before and after chemotherapy, anaemia grading, management strategies, and outcomes were collected. Haemoglobin changes were analysed using paired t-test, and differences between drug classes were assessed using one-way ANOVA. Results: Mean haemoglobin levels decreased significantly from 13.40±0.90 g/dl before chemotherapy to 9.49±1.47 g/dl after chemotherapy (mean reduction 3.91±1.65 g/dl; p<0.001). Grade 1 anaemia was observed in 52% of patients, grade 2 in 27%, grade 3 in 15%, and grade 4 in 6%. Haemoglobin reduction differed significantly among drug classes (F=5.917, p=0.0001), with greater reductions seen with alkylating agents, taxanes, and PD-1 receptor inhibitors. Iron therapy (40%) and blood transfusions (19%) were the most common management strategies. Clinical improvement was observed in 97% of patients. Conclusions: Chemotherapy causes a significant reduction in haemoglobin levels, with variability across drug classes. Regular monitoring and appropriate management of anaemia are essential during chemotherapy.